MEN’S LANGUAGE FEATURES USED IN THE NETFLIX SERIES “SEX EDUCATION”: SOCIOLINGUISTICS STUDY - Agustina, Winda; Simatupang, Ervina CM (Universitas Muhammadiyah Surakarta, 2024)
This research aims to explore the language features employed by male characters in the Netflix series